External apical root resorption after orthodontic treatment: Incidence, severity and risk factors - Fatih Bayir; Esra Bolat Gumus (Tabriz University of Medical Sciences, 2021)
Background. This study aimed to evaluate the incidence and severity of orthodontically induced inflammatory external apical root resorption (OIIEARR) and the relationship between OIIEARR and possible risk factors such as orthodontic treatment type, treatment duration, gender, and age of the patients. A further aim was to determine the prevalence of OIIEARR in different tooth groups. Methods. The study sample consisted of 1356 orthodontically treated patients (857 females and 498 males; mean age: 14.4±2.8 years). OIIEARR was evaluated using pre- and post-treatment panoramic radiographs for all the tooth groups. Teeth with severe resorption were also assessed. Patient- and treatment-related risk factors for OIIEARR were assessed statistically using Pearson's chi-squared test, independent-samples t test, and one-way ANOVA. Results. The incidence of severe root resorption following orthodontic treatment was 14.8%. Males exhibited a higher incidence of root resorption compared to females. Orthodontic treatment duration and treatment with extractions were positively correlated with OIIEARR (P<0.05). OIIEARR was observed most frequently in maxillary incisors, followed by mandibular incisors. Conclusion. Orthodontic treatment with extraction, prolonged treatment duration, and large movements of the incisors should especially be taken into consideration for OIIEARR risk. Routine radiographic follow-up during orthodontic treatment is recommended.